An objective model for diagnosing comorbid cognitive impairment in patients with epilepsy based on the clinical-EEG functional connectivity features - Ren, Zhe; Zhao, Yibo; Han, Xiong; Yue, Mengyan; Wang, Bin; Zhao, Zongya; Wen, Bin; Hong, Yang; Wang, Qi; Hong, Yingxing; Zhao, Ting; Wang, Na; et al. (Frontiers in Neuroscience, 2023)
Objective Cognitive impairment (CI) is a common disorder in patients with epilepsy (PWEs). Objective assessment method for diagnosing CI in PWEs would be beneficial in reality. This study proposed to construct a diagnostic model for CI in PWEs using the clinical and the phase locking value (PLV) functional connectivity features of the electroencephalogram (EEG). Methods PWEs who met the inclusion and exclusion criteria were divided into a cognitively normal (CON) group (n = 55) and a CI group (n = 76). The 23 clinical features and 684 PLVEEG features at the time of patient visit were screened and ranked using the Fisher score. Adaptive Boosting (AdaBoost) and Gradient Boosting Decision Tree (GBDT) were used as algorithms to construct diagnostic models of CI in PWEs either with pure clinical features, pure PLVEEG features, or combined clinical and PLVEEG features. The performance of these models was assessed using a five-fold cross-validation method. Results GBDT-built model with combined clinical and PLVEEG features performed the best with accuracy, precision, recall, F1-score, and an area under the curve (AUC) of 90.11, 93.40, 89.50, 91.39, and 0.95%. The top 5 features found to influence the model performance based on the Fisher scores were the magnetic resonance imaging (MRI) findings of the head for abnormalities, educational attainment, PLVEEG in the beta (β)-band C3-F4, seizure frequency, and PLVEEG in theta (θ)-band Fp1-Fz. A total of 12 of the top 5% of features exhibited statistically different PLVEEG features, while eight of which were PLVEEG features in the θ band. Conclusion The model constructed from the combined clinical and PLVEEG features could effectively identify CI in PWEs and possess the potential as a useful objective evaluation method. The PLVEEG in the θ band could be a potential biomarker for the complementary diagnosis of CI comorbid with epilepsy.